Comprehensive pulmonary rehabilitation in patients with bronchiolitis obliterans syndrome: A case series - Choi, Hee Eun (Respir Med Case Rep, 2020)
Chronic graft-versus-host disease (GVHD) is a significant complication of allogeneic hematopoietic stem cell transplantation, affecting 30%–70% of transplant recipients. One of the most challenging manifestations of chronic pulmonary GVHD is bronchiolitis obliterans syndrome (BOS), a rare and difficult-to-diagnose disease associated with a high mortality rate. BOS results in progressive circumferential fibrosis and, ultimately, cicatrization of the small terminal airways, manifesting as new fixed airflow obstruction. Although BOS patients are typically treated with immunosuppressive agents, there is no strong evidence that any specific therapies are effective in improving long-term outcomes. Thus, the mortality rate remains high. Therefore, there is an increasing need for additional therapies, including pulmonary rehabilitation (PR), in patients with BOS. PR is an evidence-based and comprehensive intervention for patients with chronic obstructive lung disease aimed at alleviating respiratory symptoms and optimizing functional capacity. This present case series demonstrates that comprehensive PR may also improve exercise tolerance and dyspnea in patients with BOS.